Long-term persistence with guselkumab: a 5-year multicenter retrospective study across 14 dermatology centers in Italy - Bernardini, Nicoletta; Caldarola, Giacomo; Richetta, Antonio Giovanni; Esposito, Maria; Trovato, Federica; Amerio, Paolo; Morea, Edvige; Bonifati, Claudio; Graceffa, Dario; Bruni, Pier Luigi; Giordano, Domenico; Persechino, Severino; et al. (Dermatology Practical & Conceptual, 2025)
Introduction: Psoriasis is a chronic systemic inflammatory disease that requires long-term treatment strategies to maintain sustained disease control. Treatment persistence is an important real-world indicator of therapeutic effectiveness and tolerability. Guselkumab, an IL-23 inhibitor, has shown favorable persistence in several studies, but extended long-term data remain limited.Objectives: To assess 3- and 5-year drug survival rates of guselkumab in patients with moderate-to-severe plaque psoriasis and to examine the relationship between persistence and clinical variables such as PASI, BMI, prior biologic exposure, and involvement of difficult-to-treat areas.Methods: This was a multicenter retrospective observational study conducted across 14 dermatology centers in Italy. Adult patients with moderate-to-severe plaque psoriasis who started guselkumab were included. Data collected included demographics, clinical history, disease severity, comorbidities, and treatment details. Drug survival was analyzed using Kaplan–Meier curves and Cox proportional hazards models.Results: A total of 247 patients were included. At three years, 80.2% of patients remained on guselkumab, and at five years, 72.8% continued treatment. Persistence was not significantly influenced by BMI, PASI, or age. However, prior biologics exposure was associated with a higher risk of discontinuation (hazard ratio (HR): 1.84; P=0.0208), especially in those previously treated with IL-17 inhibitors (HR:2.14; P=0.0150). The involvement of difficult-to-treat areas did not significantly affect persistence, although a trend toward reduced discontinuation was observed in patients with genital involvement (P=0.0539).Conclusions: Guselkumab demonstrated high long-term persistence in real-world clinical practice. Drug survival remained consistently high across various subgroups, with prior IL-17 inhibitor exposure being the main predictor of decreased persistence.